#TITLE_ALTERNATIVE# - Rahman Khalik (NIM 107 03 026), Donny
Abstract : Composition of triglyceride in oils is one factor that could affect stability of Total Parenteral Nutrition (TPN). Virgin coconut oil (VCO) has a suitable composition of triglycerides that could form more stable microemulsion than other conventional oils commonly used in TPN. This study was to formulate an intravenous lipid emulsion (IVLE) of VCO with target oil droplet size less <500 nm. Microemulsion formula consisted of VCO, polysorbate 80 and soybean lecithin as surfactants and gliserol as cosurfactant. Pseudoternary phase diagrams were constructed in order to determine optimum concentration range and ratio of surfactant and cosurfactant. Physical stability of the microemulsion was evaluated by freeze thaw method. pH and viscosity of the preparations were measured for 4 weeks. The best formula of microemulsion was further evaluated for its oil droplet size and flow rate through infusion system. Sterile product was prepared by final sterilization using autoclave. The pseudoternary phase diagram showed that optimum surfactant and cosurfactant concentrations were in the range of 33-44 % and 15-24 %, respectively. Freeze thaw stability results showed stable physical characteristics of the microemulsion. Mean oil droplet size was 7.1 nm and the flow rate through infusion system was 38.43 +/- 0.41 mL/min. The best formula of VCO (17%) microemulsion was achieved using 38.5% emulgator (polysorbate 80 and soybean lecithine, 10:1) and 22.25% cosurfactant (gliserol).